PENELUSURAN ALUMNI DALAM RANGKA PERSIAPAN AKREDITASI INTERNASIONAL PRODI-PRODI DI FIO UNESA - Prianto, David Agus; Pramono, Bayu Agung; Fikri, Muhammad Dzul; Arief, Nur Ahmad; Hafidz, Abdul (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Tracer Study (TS) is an effective media used to track the absorption of alumni of a university in the world of work and become an illustration of the existence of a university. The purpose of this study was to obtain alumni data for the 2019 and 2020 graduate years. This research was a descriptive quantitative type which aims to provide an overview of the current situation and work of alumni. The instrument used in this research is the google form which consists of two types of open and closed questionnaires. The sample of this research was alumni of the Faculty of Sports Science and will be mapped for each generation of alumni. The sampling technique used is quota with a target number of 300 alumni. Data analysis was carried out to produce outputs according to the research objectives, namely calculating the average value of the percentage and probability of each answer scale in the questionnaire. The conclusion was that from 710 total alumni of 2019 and 2020 graduates who have filled 310 alumni which were divided into three study programs, namely PENJAS 73 alumni from a total of 271 graduates, PKO as many as 132 alumni from 225 graduates and IKOR 105 alumni from 214 graduates. Meanwhile, those who have not filled out the PENJAS study program are 198 alumni, PKO 93 alumni and IKOR 109 alumni. As many as 41, 47% of alumni who got a job before graduating from work and 47.49% after graduating from work. The waiting period for alumni to get a job was only before 3 months after graduation with a percentage of 62%. The majority of 2019 and 2020 FIO graduates found jobs in private companies with a percentage of 40.14%.